THE ORTHODOX CHURCH AND POSTMODERNITY: IDENTITY, PLURALISM AND COMMUNION - SONEA, Cristian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2018)
The article presents the characteristics of postmodernism and its consequences on issues such as identity, pluralism and communion. As an unstable philosophical trend, it interacts with the stability and authority of the orthodox teachings, thus resulting in an ideological conflict. The article offers some theological answers to the above-mentioned conflict, as well as to some major issues of the contemporary postmodern society.